54 Early discharge for low-risk stemi patients after successful primary pci - 8-week follow-up data. (6th June 2022) - Mukherjee, Aditya; Modi, Bhavik; Bloor, Celia
Abstract : Background: Current ESC guidelines for management of patients presenting with ST-elevation myocardial infarction state that patients can be discharged after 48 hours following successful primary percutaneous coronary intervention (PCI). However, recent data have suggested it is safe to discharge selected low-risk patients 24–48 hours after successful primary PCI. We introduced an early discharge pathway for low-risk STEMI patients presenting to Glenfield Hospital and reviewed patient outcomes and feedback after 3 months (November 2021 to January 2022) of implementing the pathway. Methods: All patients undergoing primary PCI were assessed for suitability to go on the early discharge pathway at the end of the procedure. Patients fulfilling the following criteria were included in the pathway: (i) successful revascularisation with TIMI 3 flow, (ii) absence of bystander disease requiring inpatient revascularisation, (iii) absence of heart failure, (iv) stable haemodynamic parameters, (v) mobile, (vi) absence of major co-morbidities or adverse social circumstances. Suitable patients were admitted to the coronary care unit and received standard post-PCI care, including echocardiography to assess left ventricular function. Patients with LVEF> 40%, absence of further ischaemic symptoms, and no arrhythmias were deemed suitable for early discharge. All patients were given a blood pressure machine to take home and advised to check their blood pressure regularly. Follow-up was arranged in the form of a 48 h phone call and video consultations with a prescribing Advanced Nurse Practitioner at 2 and 8 weeks post-discharge. Results: During the study period, 21 patients were discharged on the early discharge pathway. The average length of inpatient stay was 35.9 hours. This was significantly less than the average inpatient stay of 79.3 hours for matched low-risk patients before introduction of the pathway. No major adverse events (death, re-infarction, or need for further revascularisation) were reported during the initial follow-up period. All patients had their blood pressure control and medications reviewed during the follow-up consultations. 61.9% of patients had their secondary prevention medications (ACEI or beta-blockers) uptitrated after the 2-week appointment. 77.7% patients had their medications uptitrated after the 8-week appointment. A patient satisfaction survey was carried out after the 8 week follow-up. The responses were overwhelmingly positive with a reduction in patients re-presenting to acute services. Conclusion: From our experience, selected low-risk patients can be safely discharged 24 hours after successful primary PCI. This results in significantly reduced inpatient stay, improved patient experience and increased bed capacity on coronary care units. It is, however, essential to have an enhanced follow-up plan in place with prescribing nurse practitioners to address any early issues. Conflict of Interest: None